The Page IS The Stage: From Picturebooks to Drama with Young Learners - Carol Serrurier-Zucker; Euriell Gobbé-Mévellec (CLELEjournal, 2014)
This paper shows the close link between picturebooks and theatre, and how the books can be dramatized with young learners. In this process the children can creatively draw on and manipulate the language they are acquiring while becoming increasingly autonomous in their learning. The task-based approach promoted by the Common European Framework of Reference for Languages (CEFR), which has shown its worth for the acquisition of communicative competences in language classes at secondary level and above, is not always easily applicable in primary classes. The young learners' often limited linguistic abilities make project work and meta-language discussion difficult in the foreign language. Teaching foreign languages through drama can provide an interesting solution. The creativity, whole-body experience and social interactivity involved in drama teaching produce high levels of motivation and an ideal method for language practice and acquisition. Storytelling is widely accepted as a valuable vector in the foreign language classroom, and allowing the young learners to become dynamically involved in the process takes it one step further. In this article we first demonstrate the inherently theatrical nature of picturebooks. The paper then reports on a project researching the use of drama in language teaching with young learners. The project commenced with drama activities inspired by two selected picturebooks, which led on to the presentation of powerful dramatic scenarios intimately relating to the children's lives.